2020
DOI: 10.1111/ffe.13301
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mode mixity and adhesive system on the fatigue life of adhesive joints

Abstract: In real applications, adhesive joints are commonly subjected to fatigue and mixed mode loading conditions. The aim of the current work is to experimentally analyse the influence of mode mixity on the fatigue strength of joints with an epoxy‐based adhesive. Different adhesive systems (acrylic and epoxies) were considered for pure mode I fatigue loading conditions. To achieve this, Arcan joints with an epoxy adhesive were manufactured and tested at different mode mixities. Based on stiffness degradation, monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…and experimental investigations in Fiber-Metal Laminates under fatigue loading using a novel trapezoidal traction-separation law. Rocha et al [177] and Sousa et al [178] investigated Mixed Mode fatigue fracture behavior for different adhesive systems and studied the effects of mode mixity. Concerning joining of dissimilar materials, Choi and Kim [179] studied the fatigue crack growth specimens with straight and penny-shaped cracks.…”
Section: Theory and Applicationmentioning
confidence: 99%
“…and experimental investigations in Fiber-Metal Laminates under fatigue loading using a novel trapezoidal traction-separation law. Rocha et al [177] and Sousa et al [178] investigated Mixed Mode fatigue fracture behavior for different adhesive systems and studied the effects of mode mixity. Concerning joining of dissimilar materials, Choi and Kim [179] studied the fatigue crack growth specimens with straight and penny-shaped cracks.…”
Section: Theory and Applicationmentioning
confidence: 99%
“…Some authors have studied the effect of loading angle on the static and fatigue response of adhesive joints 27–29 . Sousa et al 29 studied the influence of different mode mixities on the fatigue life of an epoxy‐based adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have studied the effect of loading angle on the static and fatigue response of adhesive joints. [27][28][29] Sousa et al 29 studied the influence of different mode mixities on the fatigue life of an epoxy-based adhesive. From the experimental results they concluded that the fatigue life of the joint was reduced with the introduction of a shear-loading component.…”
mentioning
confidence: 99%
“…The limit characteristics of adhesive assemblies are generally determined from the results of mechanical testing, which can be aimed either at the physical laboratory simulation of the behavior of specific assembly components under expected operating conditions or at obtaining empirical information for identification of failure criteria and models used in design and verification calculations. The latter aim can be effectively achieved by using modification of Arcan specimens [21][22][23][24][25][26][27][28][29][30][31], which enable the cleavage stress to shear stress ratio to be varied in a wide range. The test results can offer fracture loci determining the limit states of adhesive assemblies as dependent on the stress state and thermomechanical loading conditions [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The latter aim can be effectively achieved by using modification of Arcan specimens [21][22][23][24][25][26][27][28][29][30][31], which enable the cleavage stress to shear stress ratio to be varied in a wide range. The test results can offer fracture loci determining the limit states of adhesive assemblies as dependent on the stress state and thermomechanical loading conditions [30][31][32]. However, it is noted herewith that, in order to obtain correct results, it is necessary to decrease or take into account the effect of stress concentration at the specimen edges [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%